Additive Effect on Survival of Anaesthetic Cardiac Protection and Remote Ischemic Preconditioning in Cardiac Surgery: A Bayesian Network Meta-Analysis of Randomized Trials. - Alberto Zangrillo; Mario Musu; Teresa Greco; Ambra Licia Di Prima; Andrea Matteazzi; Valentina Testa; Pasquale Nardelli; Daniela Febres; Fabrizio Monaco; Maria Grazia Calabrò; Jun Ma; Gabriele Finco; et al. (PLoS ONE, 2015)
Introduction Cardioprotective properties of volatile agents and of remote ischemic preconditioning have survival effects in patients undergoing cardiac surgery. We performed a Bayesian network meta-analysis to confirm the beneficial effects of these strategies on survival in cardiac surgery, to evaluate which is the best strategy and if these strategies have additive or competitive effects. Methods Pertinent studies were independently searched in BioMedCentral, MEDLINE/PubMed, Embase, and the Cochrane Central Register (updated November 2013). A Bayesian network meta-analysis was performed. Four groups of patients were compared: total intravenous anesthesia (with or without remote ischemic preconditioning) and an anesthesia plan including volatile agents (with or without remote ischemic preconditioning). Mortality was the main investigated outcome. Results We identified 55 randomized trials published between 1991 and 2013 and including 6,921 patients undergoing cardiac surgery. The use of volatile agents (posterior mean of odds ratio = 0.50, 95% CrI 0.28-0.91) and the combination of volatile agents with remote preconditioning (posterior mean of odds ratio = 0.15, 95% CrI 0.04-0.55) were associated with a reduction in mortality when compared to total intravenous anesthesia. Posterior distribution of the probability of each treatment to be the best one, showed that the association of volatile anesthetic and remote ischemic preconditioning is the best treatment to improve short- and long-term survival after cardiac surgery, suggesting an additive effect of these two strategies. Conclusions In patients undergoing cardiac surgery, the use of volatile anesthetics and the combination of volatile agents with remote preconditioning reduce mortality when compared to TIVA and have additive effects. It is necessary to confirm these results with large, multicenter, randomized, double-blinded trials comparing these different strategies in cardiac and non-cardiac surgery, to establish which volatile agent is more protective than the others and how to best apply remote ischemic preconditioning.